Pengaruh Harga, Kepercayaan Konsumen, Dan Optimasi Penggunaan Terhadap Keputusan Pembelian Konsumen Pada Masa Pandemi Covid 19 Melalui Marketplace Tokopedia Di Kota Cimahi - Nur Hayati; Jaenal Mutaqin (POLITEKNIK LP3I JAKARTA, 2023)
This study aims to analyze whether Price, Consumer Confidence and Ease of Use have a positive and significant effect partially and simultaneously on Purchase Decisions Making through the Tokopedia marketplace during the Covid 19 pandemic in South Cimahi District, Cimahi City. The research method used is a quantitative method. While the research formula used in this study is a descriptive formula. The research sample was 130 respondents using purposive sampling technique. The technique of collecting data is through the distribution of questionnaires directly and online using an ordinal scale. The results showed that there was a partial influence of consumer trust and ease of use on purchasing decisions through the Tokopedia marketplace during the Covid 19 pandemic in South Cimahi District, Cimahi City. However, there is no partial effect of price on purchasing decisions through the Tokopedia marketplace during the Covid 19 pandemic in South Cimahi District, Cimahi City. There is a significant effect of price, consumer trust, and ease of use simultaneously on purchasing decisions through the Tokopedia marketplace during the Covid 19 pandemic in South Cimahi District, Cimahi City.Keywords: Consumer Trust, Ease of Use, Pandemic Covid 19, Purchase Decision, Price.